A new species of Tongorchestia from Bora Bora in the leeward Society Islands (Crustacea, Amphipoda, Talitridae) - Lowry, J. K.; Bopiah, Arundathi (Zootaxa, 2014)
The new species Tongorchestia borabora sp. nov. is described from Vaitape in Bora Bora, Leeward Islands, Society Islands. This is the first talitrid amphipod reported from Bora Bora and the third species of Tongorchestia from the Western Pacific oceanic islands. Currently Tongorchestia is endemic to oceanic islands in the Western Pacific.